An Unmediated Consortia Interlibrary Loan Service: The Data and Discovery of CSU+. Issue 5 (20th October 2019) - Lee, Christopher; Weldon, Meghann
Abstract: In July 2017 the California State University system of twenty-four libraries started an unmediated interlibrary loan service for print materials, known as CSU+. This paper examines four years of interlibrary loan data, from two years before CSU+'s launch to two years after, to explore the impact of the new service on interlibrary loan usage. The data shows that CSU + dramatically increased interlibrary loan use across the California State University system.